Analysis of Didactic Aspects In a Novel Titled the Witches by Roald Dahl - Mu’thia Mubasyira (Peneliti.net, 2020)
The didactic aspects can be found in various sources including in a novel. The focus of this study is to analyze cognitive, psychomotor and affective aspects in the novel. The purpose of this study is to further find out and analyze the didactic aspects contained in the novel entitled The Witches written by Roald Dahl. This study uses a descriptive qualitative approach with didactic/educational analysis.. In addition this study also aims to determine the grouping of didactic aspects based on Bloom's theory which consists of three aspects namely cognitive, affective, and psychomotor. Three aspects could not stand alone. It must be integrated each other. This reasearch is considered as qualitative research and uses descriptive analysis to perform the result data. Novel found 75 didactic quotation aspects consisting of cognitive aspects of 21 findings or 28 %, affective aspects of 21 findings or 28% and psychomotor aspects of 33 findings or 44 %. The implication of this research findings are therefore, the discovery of novel psychomotor aspects of research results is greater than affective and cognitive, so educators need to consider the use of this novel as teaching material related to motion, physical fitness and others.